The Development of Oral Reading Fluency Passages - Yuwen Chang (National Taipei University of Education, 2018)
This study aims to establish procedures for developing oral reading fluency (ORF) passages for second and third graders. The required characteristics of passages were specified and an open request for passages was announced. After experts' reviewing, 40 passages were collected. Sixty students ranging from second to fourth grade were administered 40 passages individually. Three websites were used to analyze the textual features of the passages: Chinese Learning Remedy Teaching Resources Network, Readability-Analyzing System for Chinese Articles, and Chinese Readability Index Explorer. The results indicate that the total number of different words, the number of positive conjunctions, and negative conjunctions are the most powerful predictors of oral reading fluency. Thirty-two passages were chosen based on multiple indicators. These passages were divided into two sets. Each set comprises 19 passages with six common passages for both grades. The alternate-form reliabilities for both grades are .85. The generalizability coefficients in second and third grade conditions were .94 and .95 respectively when three passages were used to estimate performance. The correlations between ORF and grade scores in Chinese are .49 and .43 respectively. The results provide evidence for supporting the preliminary reliability and validity of the test.